A prospective study on the common infectious causes of thrombocytopenia (dengue fever, leptospirosis, scrub typhus and malaria) in a tertiary care teaching hospital - G Nibandhana; Usha Kalawat; K K Sharma; Rashmi Patnayak; D T Katyarmal; Abhijit Chaudhury (Journal of Clinical and Scientific Research, 2018)
Background: The present study was undertaken to know the contribution of four infectious causes of fever namely dengue, chikungunya, scrub typhus and malaria in patients presenting with fever of more than one week duration with thrombocytopenia in a tertiary care teaching hospital, Tirupati, Andhra Pradesh. Methods: In this prospective study, 1014 samples from different patients who presented with fever and of more than one week duration and thrombocytopenia were collected over a period of six months and were processed for the detection of non-structural 1 (NS1) glycoprotein antigen for dengue, immunoglobulin M (IgM) antibodies for leptospirosis and scrub typhus by ELISA and malaria parasite by quantitative buffy coat (QBC). Results: Among 1014 samples obtained from patients with fever with thrombocytopenia, 111 (10.94%) were due to thrombocytopenia due to infectious causes. Ninety (81.08%) were due to single infection and twenty one (18.92%) due to co-infections. Males were more affected. Peak incidence was in 40-49 years of age with scrub typhus as the predominant infection. Grade-3 thrombocytopenia was more common in all the four infections. Conclusions: Our observations suggest that scrub typhus was the predominant cause of fever with thrombocytopenia, along with dengue, leptospira and malaria. Diagnostic evaluation should include search for these causes in patients presenting with fever with thrombocytopenia. This can be helpful as both are easily treatable infections with commonly available oral antibiotics.